1977
DOI: 10.1099/00221287-100-1-31
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Cycle of Chlamydia trachomatis in McCoy Cells Treated with Cytochalasin B

Abstract: The growth of a genital trachoma-inclusion conjunctivitis agent strain of Chlamydia trachomatis in McCoy cells treated with cytochalasin B was studied by quantitative infectivity estimations and by light and electron microscopy. Provided that infection of the monolayer was initiated by centrifuging the infectious particles on to the cells before incubation, this chlamydial strain grew as fast and to as high a titre [approximately 107 inclusion-forming units (i.f.u.) per culture] as those chlamydiae which infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Previous studies have demonstrated that IF staining techniques detect not only mature and immature C. trachomatis inclusions (13,14), but also the small abnormal inclusions which develop in the presence of 13-lactams (unpublished data). In this study, IF proved to be a sensitive stain for visualizing both mature inclusions and the smaller inclusions which developed when chlamydia-infected monolayers were exposed to certain concentrations of ofloxacin and tetracycline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that IF staining techniques detect not only mature and immature C. trachomatis inclusions (13,14), but also the small abnormal inclusions which develop in the presence of 13-lactams (unpublished data). In this study, IF proved to be a sensitive stain for visualizing both mature inclusions and the smaller inclusions which developed when chlamydia-infected monolayers were exposed to certain concentrations of ofloxacin and tetracycline.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to iodine and Giemsa (dark-ground microscopy), chlamydiae can be detected by immunofluorescence (IF) at all stages of their intracytoplasmic developmental cycle (13), and IF has proved to be more sensitive than Giemsa at detecting mature inclusions in cycloheximidetreated McCoy cells (14). This report describes a new method of testing drugs for in vitro antichlamydial activity by indirect IF, which is simpler but equally as sensitive as previously described techniques.…”
mentioning
confidence: 99%
“…In the case of chlamydiae special mechanisms must exist as they are taken up by HeLa or L cells 10-100 times faster than polystyrene latex particles or Escherichia coli (Byrne & Moulder, 1978). Chlamydia1 uptake requires energy from glycolysis (Kuo & Grayston, 1976) and electron microscope studies suggest that chlamydiae enter host cells by phagocytosis (Stirling & Richmond, 1977). Thus both the parasite and the host cell participate in chlamydial uptake and the stimulus for uptake must be generated at the host cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugation facilitates chlamydia1 infection, at least in part, by greatly increasing attachment; this may range from 5-to 7-fold, as with MRC4f, to more than 100-fold with other chlamydiae (Stirling & Richmond, 1977;Griffiths et al, 1976). The facilitation occurs, not through sedimentation of organisms, but from induced cell surface changes (Allan & Pearce, 1979), which may explain the failure of antibody to inhibit attachment in centrifugeassisted infection.…”
Section: Discussionmentioning
confidence: 99%